2023
DOI: 10.1002/jev2.12362
|View full text |Cite
|
Sign up to set email alerts
|

Hyaluronic acid: An overlooked extracellular vesicle contaminant

Jenifer P. Goncalves,
Raluca E. Ghebosu,
Xuan Ning Sharon Tan
et al.

Abstract: The variable presence of contaminants in extracellular vesicle (EV) samples is one of the major contributors to a lack of inter‐study reproducibility in the field. Well‐known contaminants include protein aggregates, RNA‐protein complexes and lipoproteins, which resemble EVs in shape, size and/or density. On the contrary, polysaccharides, such as hyaluronic acid (HA), have been overlooked as EV contaminants. Here, it is shown that low and medium molecular weight HA polymers are unexpectedly retained to some ext… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 62 publications
0
2
0
Order By: Relevance
“…A previous study reported possible contaminations of EV fractions with a high-molecular-weight HA fragment of 289 kDa, which could influence our measurements in this case [ 43 ]. However, the targeted up- and downregulation of HA in cells and EV by iloprost and siRNAs, respectively, and the according changes in the interaction of cells and EV with VSOP underline the validity of our conclusions.…”
Section: Discussionmentioning
confidence: 99%
“…A previous study reported possible contaminations of EV fractions with a high-molecular-weight HA fragment of 289 kDa, which could influence our measurements in this case [ 43 ]. However, the targeted up- and downregulation of HA in cells and EV by iloprost and siRNAs, respectively, and the according changes in the interaction of cells and EV with VSOP underline the validity of our conclusions.…”
Section: Discussionmentioning
confidence: 99%
“…Results from EV studies are highly impacted by the EV isolation technique used, which should also be considered in the study of the lipoprotein–EV interface. For example, it is known that the levels of co-isolated contaminants vary substantially based on the EV isolation method. , It is also critical to note that EV isolation methods may induce non-physiologically relevant interactions between EVs and lipoproteins. Ultracentrifugation, a common EV isolation technique that employs high centrifugal forces, can induce EV aggregation and alter EV morphology. , Therefore, ultracentrifugation may also cause complexation between EVs and lipoproteins.…”
Section: Ev–lipoprotein Complexesmentioning
confidence: 99%